Analisis Yuridis Pembatalan Hibah atas Harta Bersama yang Melebihi Sepertiga Bagian: Studi Putusan Pengadilan Agama Sidoarjo Nomor 3937/Pdt.G/2021/PA.Sda - Nur Aflah Husna Lubis; hasim purba; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2026)
Hibah is a legal act of transferring property rights recognized in both Islamic law and civil law. Issues arise when hibah is conducted over jointly owned property without the consent of all owners or exceeds the one-third limitation, potentially harming heirs. This normative study analyzes legal provisions, the legal consequences of hibah deeds and judicial considerations in the Sidoarjo Religious Court Decision Number 3937/Pdt.G/2021/PA.Sda. The results indicate that hibah must originate from fully owned property and is limited to one-third, as well as subject to the concept of legitime portie, so violations may result in partial or total annulment to protect the rights of entitled parties in accordance with principles of justice and legal certainty.